2020
DOI: 10.18632/aging.103249
|View full text |Cite
|
Sign up to set email alerts
|

Development of a machine learning-based multimode diagnosis system for lung cancer

Abstract: As an emerging technology, artificial intelligence has been applied to identify various physical disorders. Here, we developed a three-layer diagnosis system for lung cancer, in which three machine learning approaches including decision tree C5.0, artificial neural network (ANN) and support vector machine (SVM) were involved. The area under the curve (AUC) was employed to evaluate their decision powers. In the first layer, the AUCs of C5.0, ANN and SVM were 0.676, 0.736 and 0.640, ANN was better than C5.0 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Biomarkers and imaging are often used in combination to improve diagnostic accuracy [ 8 , 28 ], our results also showed that the efficiency has been greatly improved when CAC is combined with PNAIDS in the diagnosis of lung nodules. Correlation analysis further suggested that PNAIDS and CACs are independent of each other, which is consistent with the premise of the model that variables are independent.…”
Section: Discussionsupporting
confidence: 57%
“…Biomarkers and imaging are often used in combination to improve diagnostic accuracy [ 8 , 28 ], our results also showed that the efficiency has been greatly improved when CAC is combined with PNAIDS in the diagnosis of lung nodules. Correlation analysis further suggested that PNAIDS and CACs are independent of each other, which is consistent with the premise of the model that variables are independent.…”
Section: Discussionsupporting
confidence: 57%
“…In lung cancer, mixed models combining multiple factors have been shown to provide excellent prognostic benefits 12,13 . At present, many studies have tried to establish models to achieve the intelligent identification of benign and malignant nodules, and have shown that machine learning plays an irreplaceable role in disease diagnosis 14,15 …”
Section: Introductionmentioning
confidence: 99%
“…Machine learning (ML), a branch of artificial intelligence and computer science, focusing on simulating the way the human brain learns using statistics and algorithms to improve accuracy, has had an outstanding performance in disease diagnosis, prognosis prediction, antitumor drug response, and treatment response assessment [20][21][22][23][24][25]. However, studies evaluating tumor response in LARC after NAT using ML algorithms are limited.…”
Section: Introductionmentioning
confidence: 99%